Vad är urfolksmetodologier? - Sehlin MacNeil, Kristina (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
Many indigenous researchers have described Indigenous Methodologies as alternative ways of thinking about research processes. This article aims to give an introduction to Indigenous Methodologies and to locate them in relation to the qualitative research field. In addition epistemological aspects of indigenous research models are contrasted with mainstream Western approaches in order to open up for a conversation on the use of multiple epistemologies. The article concludes with a discussion on whom Indigenous Methodologies are available to and poses the hopeful proposition that space might be created for Indigenous Methodologies within mainstream academia.